Romania's Regional Development by Supporting the Agricultural Sector - Irrigation System Influencing Factor - Ioana PANAIT; Marian Catalin CUCU (Communications of International Proceedings, 2020)
The realization of a modern and extended irrigation system to irrigate larger agricultural areas is necessary due to the conditions faced by the Romanian regions in terms of weather factors but must be done in a responsible and efficient manner that will lead to a development of the Romanian agricultural sector. Accelerate the adaptation of irrigation infrastructure to the needs of farmers to reduce the vulnerability of agricultural production to external climatic factors and develop economic viability for farms by ensuring a socio-economic balance while ensuring environmental protection. Rural development contributes to regional development and reducing interregional gaps. In Romania, agriculture is a common activity in the lives of people in rural areas, so this paper aims to highlight the importance of a well-developed irrigation system in the context of agriculture's dependence on weather conditions. Agriculture recorded a significant increase in production in the period 1997-2019 due to research, development and innovation in the field, but continues to be an activity largely dependent on nature.
Keywords: Competitiveness; Economic Growth; Irrigation Infrastructure.